Pengaruh Metode Latihan High Intensity Interval Training (HIIT) Terhadap Tingkat Kapasitas Kerja Maksimal (VO2Max) Pemain Futsal SMAN 10 Bogor - Fachrezi, Muhammad Fachru; Irawan, Roy Januardi; Widodo, Achmad; Kafrawi, Fatkur Rohman (Universitas Hamzanwadi, 2024)
This study aims to measure the increase in maximum work capacity (vo2max) of futsal players through the training method given in the form of high intensity interval training method within a period of 5 to 6 weeks. The population in this study were 25 futsal athletes and a sample of 15 athletes sampling techniques using quota sampling. Testing using pretest and posttest with experimental methods in one group. Non-probability sampling is one form of data sampling. At the same time, pre- and post-tests are used in data collection techniques. This study shows the results that vo2max significantly increased by 1.01% in the sample after being given HIIT training treatment for 6 weeks. The increase was evidenced by an increase in the average pretest and posttest scores. The average value of the first test was 48.19 ml/kg/minute, while the last test was 49.20. The difference in training with the HIIT training method, when combined with other physical exercises, emphasizes the importance of increasing the intensity of exercise to increase the heart rate beyond its maximum limit during exercise.